Pemeriksaan Kesehatan dan Edukasi Pencegahan Penyakit Diabetes pada Lansia - Zaman, Badrul; Rabial, Jihan; Veriana, Cut Maria; Jumiati, Jumiati; Nurhidayat, Nurhidayat; Hidayat, Muhammad; Sari, Novita (-, 2025)
Older adults are a group with the highest risk of developing diabetes due to physiological changes, lifestyle factors, and comorbidities. Early detection through health examinations and increasing knowledge through preventive education are strategic steps to reduce the incidence and complications of diabetes in the elderly population. The purpose of this community service is to enhance the understanding of older adults regarding Health Screening and Diabetes Prevention Education in Jangka Alue Village, Jangka Subdistrict, Bireuen Regency. The method used in this community service activity is counseling. Results: Providing education and guidance in raising community awareness. Conclusion: After the implementation of this community service, the community was able to adopt a healthy lifestyle and diet, as well as educate others about diabetes in order to prevent and increase awareness in addressing this health problem.